Religion and earnings: evidence from Germany. Issue 8 (8th August 2016) - Sinnewe, Elisabeth; Kortt, Michael; Steen, Todd
Abstract : Purpose: To estimate the association between religious affiliation and the rate of return to human capital for German men and women. Design/methodology/approach: This paper employs data from the 1997, 2003, 2007, and 2011 waves of the German Socio-Economic Panel for German men and women in full-time employment between the age of 25 and 54. The association between religious affiliation and wages was estimated using a conventional human capital model. Findings: This paper finds that Catholic men (women) received a wage premium of 4% (3%) relative to their Protestant counterparts, even after controlling for an extensive range of demographic, economic and social characteristics. Originality/value: Our study contributes to the literature by providing – to the best of our knowledge – the first results on the wage premium received by Catholic men and women in the German labour